Analisis Pengaruh Rasio Early Warning System dan Good Corporate Governance terhadap Risk Based Capital pada Perusahaan Asuransi Syariah di Indonesia Periode 2017-2021 - Auliya Diasyasifa; Fatmi Hadiani; Banter Laksana (Journal of Applied Islamic Economics and Finance, 2023)
The goal of this study is to determine how big of an impact Good Corporate Governance (GCG) and Early Warning System (EWS) ratios have on the Risk Based Capital (RBC) of Sharia insurance businesses. The study technique employs a total sample of 13 Islamic insurance firms and a quantitative approach using panel data regression models utilizing EViews12. Liquidity, claims expenditure, and changes in surplus are the factors from the EWS ratio that were chosen. The size of the board of directors, board of commissioners, sharia supervisory board, and audit committee are the following factors that were chosen from GCG. The outcome of the hypothesis test was that none of the independent factors concurrently affected the RBC variable. The liquidity ratio is the single factor that, in part, significantly affects RBC. Keywords: EWS; GCG; RBC; Sharia Insurance